Life and Times of Jo Mora Iconic Artist of the American West. - Hiller, Peter (Gibbs Smith, 2021)
Jo Mora (1876-1947) lived the Western life he depicted in his prolific body of visual art. The magnitude of Mora's insights into his life and work, as described in his own words-many presented here in this book-cannot be underestimated. Peter Hiller's thoughtful presentation of Jo Mora's life is seen here in all of its creative glory.